Development of translating ribosome affinity purification for zebrafish. Issue 3 (26th February 2013) - Tryon, Robert C.; Pisat, Nilambari; Johnson, Stephen L.; Dougherty, Joseph D.
<x xml:space="preserve">Abstract</x> The regulation of transcription and translation by specific cell types is essential to generate the cellular diversity that typifies complex multicellular organisms. Tagging and purification of ribosomal proteins has been shown to be an innovative and effective means of characterizing the ribosome bound transcriptome of highly specific cell populations in vivo. To test the feasibility of using translating ribosome affinity purification (TRAP) in zebrafish, we have generated both a ubiquitous TRAP line and a melanocyte‐specific TRAP line using the native zebrafish rpl10a ribosomal protein. We have demonstrated the capacity to capture mRNA transcripts bound to ribosomes, and confirmed the expected enrichment of melanocyte specific genes and depletion of non‐melanocyte genes when expressing the TRAP construct with a cell specific promoter. We have also generated a generic EGFP‐rpl10a Tol2 plasmid construct (Tol2‐zTRAP) that can be readily modified to target any additional cell populations with characterized promoters in zebrafish. genesis 51:187–192, 2013. © 2012 Wiley Periodicals, Inc.